Use of Cefiderocol in Management of Resistant Gram-Negative Infections in Patients Admitted to a Burn Center - Lindey C. Lane; Jonathon K. Walker; David M. Hill (Microorganisms, 2025)
Cefiderocol is a novel cephalosporin antibiotic approved for urinary tract infections and hospital-acquired or ventilator-associated pneumonias caused by difficult-to-treat Gram-negative pathogens. To date, its use in treating difficult-to-treat Gram-negative infections in burn patients has been minimally described in the literature. Our aim was to evaluate cefiderocol use in a population of burn patients initiated on cefiderocol for resistant Gram-negative infections. A retrospective chart review of nine patients was conducted. Two patients were treated for pneumonia; five for bacteremia, three of which had coexisting burn wound infections or pneumonia; one was treated for a burn wound infection alone; and one patient was treated for a simultaneous burn wound infection, pneumonia, and bacteremia. The pathogens treated included the following: multidrug-resistant Pseudomonas aeruginosa, carbapenem-resistant Acinetobacter baumannii, and carbapenem-resistant Enterobacterales. Three isolates were confirmed as New Delhi metallo-beta-lactamase (NDM) producers, though this was likely an underestimate as genetic testing is not routinely performed at our institution and not all the isolates were tested. One of the nine patients in this study succumbed to their infection. Of note, the multidrug-resistant Pseudomonas aeruginosa in this patient tested intermediate to cefiderocol. The patients were treated with cefiderocol for a median of 14 days, most commonly in combination with other antimicrobial therapies. Treatment with cefiderocol appeared to be efficacious in this population of burn patients when other antibiotics routinely used for complicated infections caused by multidrug-resistant (MDR) Gram-negative pathogens showed treatment failure or resistance.